Physical geography contributes. (February 2020) - Harden, Carol P; Luzzadder-Beach, Sheryl; MacDonald, Glen M; Marston, Richard A; Winkler, Julie A
Physical geography is a process, conducted by people, of integration and synthesis of ideas and observations to advance scientific understanding of Earth's surface and atmosphere and to apply this knowledge to the greater good of the planet and its people. Therefore, physical geography matters; that is, physical geography makes a difference to people and contributes to environmental decision making at various scales. Based upon presentations and discussion at the 2019 AAG Annual Meeting (see editorial above in this issue), we provide here a historical perspective and distillation of how and why, in our opinions, physical geography matters. Although we provide several specific examples, these represent only a small portion of the large body of excellent and relevant physical geography research.